2021
DOI: 10.1111/ppc.12940
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' perceived stress: Interaction with emotional intelligence and self‐leadership

Abstract: Purpose The aim of the current study was to determine how emotional intelligence and self‐leadership levels could be related to perceived stress. Design and Methods A total of 341 nursing students were enrolled in this descriptive correlational study. Study measures included a sociodemographic form, Emotional Intelligence Evaluation Scale, Revised Self‐Leadership Questionnaire, and Perceived Stress Scale for Nursing Students. Findings Results showed that ‘‘assignments and workload’’ as well as “taking care of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…This study identified a slight statistically significant relationship between SL levels and age, which is inconsistent with other studies indicating no relationship between age and SL 14,34,36 . These data suggest that maturity may bring broader life experiences, acquired knowledge, and responsibilities in increasing levels of SL 49 …”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This study identified a slight statistically significant relationship between SL levels and age, which is inconsistent with other studies indicating no relationship between age and SL 14,34,36 . These data suggest that maturity may bring broader life experiences, acquired knowledge, and responsibilities in increasing levels of SL 49 …”
Section: Discussioncontrasting
confidence: 99%
“…Published studies on SL among nurses were identified from countries outside the United States including South Korea, [23][24][25][26][27][28][29][30][31][32] , South Africa, 33 Turkey, 12,14 Iran, 34 Egypt, 35 Lesotho, 36 and Sri Lanka. 37 Results from a few of these international studies include nurses' communication capabilities and SL being connected, 24,25,28 a positive relationship between job performance and SL, 14,24,28 communication competence impacting SL, 25,28 a positive relationship between knowledgesharing behavior and innovative work behavior and SL, 37 a positive relationship among nursing students' SL and their perception of learning, 26 a negative relationship between burnout and SL, 24,26 and nurses' SL levels predicting nurses providing person-centered care for oncology patients. 27 Two studies in Korea reported a correlation (r = −0.42, P < 0.01) between SL and burnout among nurses; thus, when SL levels increased, burnout declined.…”
Section: Sl In Nursingmentioning
confidence: 99%
See 3 more Smart Citations